2014
DOI: 10.1007/s00520-014-2281-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life and malnutrition in patients treated for oral cancer

Abstract: PurposeThis study examined whether oral health-related quality of life (OHRQoL) is associated with nutritional status in patients treated for oral cancer.MethodsA cross-sectional study was carried out on with patients treated for oral cancer at least 6 months after treatment. OHRQoL was measured using two questionnaires: Oral Impacts on Daily Performances (OIDP) and Oral Health Impact Profile (OHIP-14); malnutrition risk was assessed through the Mini Nutritional Assessment (MNA). Multivariable regression model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 27 publications
3
33
0
3
Order By: Relevance
“…The main factors involved in the development of malnutrition in these patients are metabolic abnormalities and nutrition impact symptoms (NIS), which can be related to the tumor itself or can occur as side effects of anticancer treatment . Aging promotes changes in body composition, metabolic and physiological changes, and reduced functional capacity, making older patients with cancer who are undergoing oncological treatment more vulnerable, resulting in increased morbidity and mortality …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors involved in the development of malnutrition in these patients are metabolic abnormalities and nutrition impact symptoms (NIS), which can be related to the tumor itself or can occur as side effects of anticancer treatment . Aging promotes changes in body composition, metabolic and physiological changes, and reduced functional capacity, making older patients with cancer who are undergoing oncological treatment more vulnerable, resulting in increased morbidity and mortality …”
Section: Introductionmentioning
confidence: 99%
“…19,20 Aging promotes changes in body composition, metabolic and physiological changes, and reduced functional capacity, 21 making older patients with cancer who are undergoing oncological treatment more vulnerable, resulting in increased morbidity and mortality. [22][23][24][25] Currently, the prevalence of malnutrition among older Brazilians with cancer and the prevalence of NIS as risk factors for malnutrition in these patients is unclear. We hypothesized that the prevalence of malnutrition and NIS would be greater in older versus younger adult patients with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a large proportion of respondents experienced pain (60%), discomfort in chewing (70%), the need to interrupt meals (62%), an unsatisfactory diet (50%), and oral dryness (83.4%). Barrios et al 13 reported that reduced OHRQoL in HaNC patients was strongly associated with eating. The majority of the participants in the present study were patients with cancer affecting the oral cavity and so they would have experienced a direct effect from ionizing radiation.…”
Section: Patients' Ohrqolmentioning
confidence: 99%
“…The two generic OHRQoL measures most widely used are the oral health impact profile (OHIP-14) and the oral impacts on daily performances (OIDP). 9 Among oral cancer patients, dysphagia and treatmentrelated problems, such as mucositis and nausea, are common. Due to these problems, food intake is often diminished, leading to unintentional weight loss, and malnutrition.…”
Section: Introductionmentioning
confidence: 99%